Application of iron-doped carbon nitride rich in nitrogen vacancy
By developing a new photocatalytic system combining iron-doped carbon nitride with nitrogen-rich vacancies and UV-LED/NaClO and UV-LED/NH2Cl systems, the removal effect of carbamazepine and other difficult-to-degrade drug active compounds in the prior art has been solved. The problem of insufficient achieves the effect of significantly improving the removal rate and reaction rate.
Patent Information
- Application Number
- CN202411444464.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-07
AI Technical Summary
The existing UV-LED/NaClO and UV-LED/NH2Cl processes are insufficient in removing active compounds that are difficult to degrade drug, such as carbamazepine, and it is necessary to improve the removal efficiency to deal with environmental safety threats.
Develop a nitrogen-rich vacancies-rich iron-doped carbon nitride (Fe-g-C3N4-Nv) to form a new photocatalytic system to enhance the drug Degradation efficacy of active compounds.
The removal rate of carbamazepine by UV-LED/NaClO and UV-LED/NH2Cl systems was significantly improved. The removal rate of UV-LED/NaClO/Fe-g-C3N4-Nv system was as high as 98.3%, and UV-LED/NH2Cl/ The removal rate of the Fe-g-C3N4-Nv system is as high as 67.2%, and the reaction rate constant is increased.
Smart Images

Figure CN119386913A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of degradation of active pharmaceutical compounds, and in particular to application of iron-doped carbon nitride rich in nitrogen vacancies. Background Art
[0002] As an emerging aquatic environmental pollutant, pharmaceutically active compounds (PhACs) have attracted great attention due to their potential risks to human health and the ecological environment. PhACs molecules contain a large number of functional groups, such as aldehyde, carboxyl and amino groups, which make them highly polar and have poor adsorption properties. In addition, conventional sewage treatment processes are difficult to remove PhACs from water, making PhACs persistent, bioaccumulative and biotoxic in the ecosystem. Among them, carbamazepine (CBZ), as a pharmaceutically active compound with environmental persistence and bioaccumulative effects, poses a potential threat to ecological security and human health. Traditional treatment processes cannot effectively remove it, and the environmental safety issues it causes are gradually becoming a key factor restricting the high-quality and sustainable development of various countries. Developing advanced drinking water treatment technology is an effective countermeasure to deal with water quality deterioration and prevent major environmental risks.
[0003] Chlorine-based disinfectants based advanced oxidation processes (Cl-AOPs) are considered to be ideal for simultaneous disinfection and removal of pharmaceutically active compounds, among which UV-LED / NaClO process and UV-LED / NH 2 Cl process has attracted much attention as a new type of AOPs. 2 The Cl process has been studied at laboratory and pilot scale and is expected to achieve efficient reduction of pharmaceutical active compounds in drinking water treatment projects due to: 1) the synergistic effect of chlorine-based disinfectants and UV-LED irradiation can produce broad-spectrum oxidative species hydroxyl radicals (HO·) and highly selective reactive chlorine / nitrogen species (RCS / RNS); 2) no additional infrastructure construction and chemical reagents are required; 3) chlorine and chloramines can provide residual protection without the need for additional quenching removal. However, the UV-LED / NaClO process and UV-LED / NH 2 The removal effect of Cl process on the active compounds of refractory drugs such as carbamazepine is negligible. The removal efficiency of target pollutants is improved by UV-LED / NaClO process and UV-LED / NH 2 It is an inevitable trend of Cl process development.
[0004] The Chinese patent with publication number CN112158910A recently applied by the applicant discloses a method for treating antiepileptic drugs in water using a novel photo-Fenton system, comprising the following steps: step 1: mixing a NaClO solution and a carbamazepine aqueous solution to obtain a mixed solution 1, and transferring the mixed solution 1 to a reaction dish; step 2: adjusting the pH of the mixed solution 1 to 3-5; step 3: adding an Fe (III) solution to the reaction dish in step 2 to obtain a mixed solution 2; step 4: placing the reaction dish under a UV-LED device, reacting for a certain period of time under stirring conditions, and achieving the removal of carbamazepine in the water; UV-LED irradiation can effectively activate Fe (III) and NaClO aqueous solutions, and the generated HO· and RCS can oxidize CBZ in the water, achieving efficient removal of CBZ in a shorter time, greatly reducing the energy consumption of UV-LED and the cost of oxidants, and the above method of the invention is simple to operate and easy to implement.
[0005] The Chinese patent with the authorization announcement number CN111453804B discloses a method for preparing an iron-doped graphite-like carbon nitride / graphene multifunctional nanocomposite material, wherein urea and ferric chloride hexahydrate are dissolved in anhydrous ethanol, stirred and evaporated to obtain a primary composite material; calcined once in a muffle furnace, cooled, ground and cleaned; then placed in a tube furnace, calcined and thermally stripped twice to obtain an iron-doped graphite-like carbon nitride nanocomposite material; the obtained iron-doped graphite-like carbon nitride nanocomposite material is subjected to hydrothermal reaction with an ultrasonically dispersed graphene ethanol solution, and then dried and ground to obtain an iron-doped graphite-like carbon nitride / graphene multifunctional nanocomposite material. The iron-doped graphite-like carbon nitride / graphene multifunctional nanocomposite material prepared by the above method reduces the recombination rate of photogenerated electrons and holes, improves the light response ability, has a significant Fenton-like oxidation / visible light photocatalytic oxidation synergistic degradation effect, has a good synergistic decontamination function, and has a significant removal effect when adsorbing and degrading typical dyes (Rhodamine B).
[0006] Currently, the trend is towards UV-LED / NaClO process or UV-LED / NH 2 The introduction of photocatalysts into the Cl process to construct a new heterogeneous photocatalytic system provides a reliable technical option for the treatment of active pharmaceutical compounds. The synthesis of an efficient and stable photocatalyst has become the core of the development of this system. Due to the high abundance, low price and wide application of iron in traditional Fenton systems, it provides the possibility for the construction of this new heterogeneous photocatalytic system. To prevent metal precipitation, the loading substrate must have strong stability to iron ions. The two-dimensional material gC 3 N 4 The stable metal-N bond in gC provides a promising solution. 3 N 4Since CN forms a π-conjugated plane, the weak van der Waals interaction between these layers leads to unfavorable interlayer charge transport, and photogenerated electrons and holes are very easy to recombine. Iron doping can be achieved by modifying gC 3 N 4 The electronic structure of gC improves the efficiency of photogenerated carrier separation. 3 N 4 The photocatalytic performance of Fe-doped carbon nitride (Fe-gC) is improved by using nitrogen vacancies. However, the metal sites are still easily lost or aggregated in long-term operation, resulting in reduced activity. Surface defect engineering is an effective modification strategy for building long-life photocatalysts. The introduction of nitrogen vacancies can adjust the band structure and generate a large number of unpaired electrons. Nitrogen vacancies can serve as electron sources for iron sites and significantly improve the stability of metal sites. Therefore, a novel Fe-doped carbon nitride (Fe-gC) with nitrogen vacancies was developed. 3 N 4 -Nv) simultaneously enhances UV-LED / NaClO and UV-LED / NH 2 The method of degrading the efficacy of typical pharmaceutical active compounds by Cl system is an urgent problem to be solved. Summary of the invention
[0007] The problem to be solved by the present invention is to provide an application of iron-doped carbon nitride rich in nitrogen vacancies in view of the above-mentioned deficiencies in the prior art, which has the advantages of simultaneously enhancing the UV-LED / NaClO degradation system and the UV-LED / NH 2 The advantages of Cl degradation system in degradation of typical pharmaceutical active compounds (CBZ).
[0008] The above-mentioned object of the present invention is achieved through the following technical solutions: Application of iron-doped carbon nitride rich in nitrogen vacancies based on UV-LED / NaClO and / or UV-LED / NH 2 The invention discloses a degradation system of Cl, and application of the iron-doped carbon nitride rich in nitrogen vacancies in the degradation of pharmaceutically active compounds.
[0009] Furthermore, the preparation process of the nitrogen vacancy-rich iron-doped carbon nitride comprises firstly reacting urea and FeCl 3 6H 2 O is dissolved in deionized water and stirred to mix, and then the water is evaporated and ground, and then calcined in a muffle furnace, cooled and ground after the calcination, and then calcined in a tubular furnace under a nitrogen atmosphere, and cooled and ground after the calcination to obtain iron-doped carbon nitride rich in nitrogen vacancies.
[0010] Furthermore, the urea and FeCl 3 6H 2 The mass ratio of O is 100:1.
[0011] Furthermore, the stirring time for the stirring and mixing is 60 minutes and the stirring rate is 150 r / min.
[0012] Furthermore, the evaporation temperature of the evaporated water is 80° C. until the water is completely evaporated.
[0013] Furthermore, the calcination temperature of the muffle furnace calcination is ≥575°C, the heating rate is 1-10°C / min, and the calcination time is ≥4h.
[0014] Furthermore, the calcination temperature of the tubular furnace calcination is ≥650°C, the heating rate is 1-10°C / min, and the calcination time is ≥4h.
[0015] Furthermore, the pharmaceutically active compound is carbamazepine.
[0016] Furthermore, in the process of degrading the pharmaceutically active compound, the iron-doped carbon nitride rich in nitrogen vacancies is first added to a solution containing the pharmaceutically active compound, and adsorbed by stirring under dark conditions, and then NaClO and / or NH 2 Cl forms a degradation system and undergoes photocatalytic degradation reaction under UV-LED irradiation, and iron-doped carbon nitride rich in nitrogen vacancies is recovered after the reaction.
[0017] Furthermore, the concentration of the active pharmaceutical compound in the degradation system is 1-10 mg / L, the concentration of the iron-doped carbon nitride rich in nitrogen vacancies is 50-400 mg / L, and the concentration of Cl - The concentration is 25~400μmol / L.
[0018] Furthermore, the stirring time of the stirring adsorption is 30 minutes and the stirring rate is 150 r / min.
[0019] Furthermore, the UV-LED light source wavelength of the photocatalytic degradation reaction is 278nm, the reaction temperature is 10-45°C, the reaction pH is 3-11, and the reaction time is ≥20min.
[0020] Furthermore, the specific implementation method of recovering the iron-doped carbon nitride rich in nitrogen vacancies is that after the reaction is completed, the reaction liquid of the degradation system is filtered, the filter residue is washed with deionized water and ethanol for multiple times, and then dried at 80° C. to recover the iron-doped carbon nitride rich in nitrogen vacancies.
[0021] In summary, the beneficial technical effects of the present invention are: 1. Fe-gC of the present invention 3 N 4 The morphology of -Nv is a tightly stacked flake structure with a size of several microns. The doping of iron and the introduction of nitrogen vacancies do not change the gC 3N 4 The sheet structure of Fe-gC 3 N 4 No iron oxide nanoparticles were found in gC-Nv, further indicating that iron has been doped into gC 3 N 4 In the framework, the doping of iron and the introduction of nitrogen vacancies improve the gC 3 N 4 The specific surface area provides more active sites for the adsorption and photocatalytic degradation of target pollutants; 2. The present invention accurately synthesizes Fe-gC by secondary calcination method 3 N 4 -Nv, used to enhance UV-LED / NaClO system and UV-LED / NH 2 Degradation efficiency of Cl system for pharmaceutically active compounds; Fe sites are doped into gC in the form of Fe-N 3 N 4 In the framework, the introduction of nitrogen vacancies plays the role of electron traps; Fe-gC 3 N 4 -There are multiple charge transfer pathways on Nv, which significantly improves the separation and transfer efficiency of photogenerated charges; 3. gC of the present invention 3 N 4 It is a non-metallic semiconductor composed of only C and N elements, with a band gap of about 2.7 eV. It can absorb and utilize visible light. As an emerging photocatalyst, gC 3 N 4 Provides new opportunities for developing nanomaterials with unique electronic catalytic properties; gC 3 N 4 The structural unit is an N-bridged triazine or triazine ring, in which the highly electronegative N is replaced by C and is highly symmetrical, resulting in slow internal electron transport. It is worth noting that, since CN forms a π-conjugated plane, the delocalized photogenerated charge is located in gC 3 N 4 The weak van der Waals interaction between these layers leads to unfavorable interlayer charge transfer and low efficiency of photogenerated carrier separation; metal element doping can further adjust gC 3 N 4 The band gap structure of Fe 2 + As a commonly used cheap catalyst in advanced oxidation processes, HO· and Cl· can react with Fe 2 + In situ Fe formation 3 + and simultaneously; This provides the possibility for the application of iron-based heterogeneous catalysts in UV-LED / NaClO process, Fe-gC 3N 4 It has shown excellent catalytic performance in the field of environmental remediation; in addition, given that gC 3 N 4 It is mainly composed of CN bonds, and it is very easy to form defects in its structure. Defect engineering has been proven to achieve effective charge separation and migration by guiding internal electron arrangement, changing surface microstructure or generating new identical electron excitation orbits. Among these defects, nitrogen vacancies show unique advantages in generating new defect energy levels, enhancing light absorption, accelerating carrier separation and promoting photogenerated hole accumulation. 3 N 4 -Nv system, O 2 · - Through the efficient activation of NaClO, it can be converted into HO· and Cl· with stronger oxidizing ability; hvb + For H 2 The oxidation of O / OH- and the activation of HOCl / OCl- increased the yields of HO· and Cl·. 2 Cl / Fe-gC 3 N 4 -Nv system, O 2 · - Can break NH 2 The N-Cl bond in Cl generates NH 2 · and Cl·; NH 2 ·With O 2 Binding can be converted into NH 2 OO·, NO· and NO 2 ·;hvb + NH 2 Cl is oxidized to form NHCl· and NHClOO·; O 2 · - and hvb + By NH 2 The full activation of Cl promotes the generation of HO· and RNS, while HO· and RNS dominate the degradation of CBZ in the system; therefore, the Fe-gC 3 N 4 -Nv can realize NaClO / NH 2 Highly efficient activation of Cl to remove typical pharmaceutically active compounds from water; 4. This invention proposes for the first time a Fe-gC 3 N 4 -Nv new photocatalytic system; Fe-gC 3 N 4 -Nv can enhance both UV-LED / NaClO process and UV-LED / NH2 Cl process for degradation of typical pharmaceutical active compounds; UV-LED / NaClO / Fe-gC 3 N 4 -Nv system and UV-LED / NH 2 Cl / Fe-gC 3 N 4 The removal rates of carbamazepine by the -Nv system were as high as 98.3% and 67.2%, respectively, and the reaction rate constants were higher than those of the UV-LED / NaClO process and UV-LED / NH 2 Cl process increased by 13.7 and 8.8 times respectively; 5. Fe-gC of the present invention 3 N 4 -Fe doping in Nv enhances gC 3 N 4 The oxidation ability of the metal is enhanced, and the introduction of nitrogen vacancies forms a new intermediate energy level and acts as an electron trap; 6. Fe-gC of the present invention 3 N 4 -Nv forms a new electron transmission channel under the combined action of iron doping and nitrogen vacancies, significantly improving the electron migration rate and the separation efficiency of photogenerated carriers; 7. Fe-gC of the present invention 3 N 4 -Nv under UV-LED irradiation through O 2 · - and hvb + To achieve NaClO and NH 2 The efficient activation of Cl improves the yields of HO·, RCS, and RNS in the system; 8. UV-LED / NaClO / Fe-gC developed by the present invention 3 N 4 -Nv system and UV-LED / NH 2 Cl / Fe-gC 3 N 4 The -Nv system has strong adaptability to water quality fluctuations and can achieve stable degradation of carbamazepine. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is the Fe-gC of Example 1 of the present invention. 3 N 4 -X-ray diffraction pattern of Nv.
[0023] Figure 2 It is the Fe-gC of Example 1 of the present invention. 3 N 4-Nitrogen adsorption-desorption test results and pore size distribution diagram of Nv.
[0024] Figure 3 It is the Fe-gC of Example 1 of the present invention. 3 N 4 -Fourier transform infrared absorption spectrum of Nv.
[0025] Figure 4 It is the Fe-gC of Example 1 of the present invention. 3 N 4 -Electron paramagnetic resonance spectrum of Nv.
[0026] Figure 5 It is a comparison chart of the degradation efficiency of carbamazepine in Example 1 of the present invention and Comparative Examples 1 to 6.
[0027] Figure 6 3 is a graph showing the changes in the removal rates of carbamazepine in Examples 1, 11, 12, 15 and 17 of the present invention.
[0028] Figure 7 It is a graph showing the changes in the removal rates of carbamazepine in Examples 1 and 34 to 38 of the present invention.
[0029] Figure 8 It is a graph showing the changes in the removal rates of carbamazepine in Examples 1, 40 to 43 of the present invention. DETAILED DESCRIPTION
[0030] In order to make the technical means, creative features, objectives and functions achieved by the present invention clearer and easier to understand, the present invention is further explained below in conjunction with the accompanying drawings and specific implementation methods. Example
[0031] Example 1: Application of iron-doped carbon nitride rich in nitrogen vacancies disclosed in the present invention. Specifically, based on UV-LED / NaClO and / or UV-LED / NH 2 The invention discloses a degradation system of Cl, and an application of iron-doped carbon nitride rich in nitrogen vacancies in the degradation of pharmaceutically active compounds, wherein the pharmaceutically active compound is carbamazepine.
[0032] The specific implementation method of this embodiment is: S1 Preparation of Nitrogen-Vacancy-Rich Iron-Doped Carbon Nitride: First, 10 g urea and 0.1 g FeCl 3 6H 2O was dissolved in 50 mL of deionized water, and the mixture was stirred at 150 r / min for 60 min, and then continued to be stirred in a water bath at 80 ° C until the water was completely evaporated. After the evaporated mixture was ground, it was placed in a muffle furnace for calcination, and the calcination temperature of the muffle furnace was controlled to be 575 ° C, the heating rate was 2.5 ° C / min, and the calcination time was 4 h. After the calcination, it was cooled to room temperature and ground to obtain a precursor, which was then placed in an uncovered crucible and calcined in a tubular furnace under a nitrogen atmosphere. The calcination temperature of the tubular furnace was controlled to be 650 ° C, the heating rate was 2.50 ° C / min, and the calcination time was 4 h. After the calcination, it was cooled to room temperature and ground to obtain nitrogen-vacancies-rich iron-doped carbon nitride (Fe-gC 3 N 4 -Nv); S2: preparing a solution containing a pharmaceutically active compound: dissolving carbamazepine in 100 mL of water to obtain a 10 mg / L solution containing a pharmaceutically active compound.
[0033] S3 degrades the active pharmaceutical compound: firstly, Fe-gC 3 N 4 -Nv is added to the solution containing the pharmaceutically active compound obtained by S2 to control the Fe-gC 3 N 4 -Nv concentration was 200 mg / L, and the mixture was stirred at 150 r / min for 30 min, and then NaClO or NH 2 Cl forms a degradation system to control Cl - The concentration is 100 μmol / L (calculated as available chlorine. The available chlorine concentration of NaClO is determined by a residual chlorine meter. 2 The concentration of Cl was determined by N,N-diethyl-p-phenylenediamine spectrophotometry), and then a photocatalytic degradation reaction was carried out under UV-LED irradiation, and the UV-LED light source wavelength of the photocatalytic degradation reaction was controlled to be 278 nm, the reaction temperature was 25°C, the reaction pH was 7, and the reaction time was 20 min. After the reaction was completed, the reaction liquid of the degradation system was filtered, and the filtrate was the degradation solution after the degradation of carbamazepine. The filter residue was washed with deionized water and ethanol for multiple times, and then dried at 80°C to recover iron-doped carbon nitride rich in nitrogen vacancies.
[0034] Examples 2 to 10 are applications of iron-doped carbon nitride rich in nitrogen vacancies disclosed in the present invention. The difference from Example 1 is that in S2, carbamazepine is dissolved in 100 mL of water to obtain solutions containing 1, 2, 3, 4, 5, 6, 7, 8, and 9 mg / L of pharmaceutically active compounds.
[0035] Examples 11 to 17 are applications of iron-doped carbon nitride rich in nitrogen vacancies disclosed in the present invention. The difference from Example 1 is that in S3, the Fe-gC 3 N 4 -Nv concentration is 50, 100, 150, 250, 300, 350, 400 mg / L.
[0036] Embodiments 18 to 25 are applications of iron-doped carbon nitride rich in nitrogen vacancies disclosed in the present invention. The difference from Embodiment 1 is that in S3, Cl is controlled - The concentrations are 25, 50, 150, 200, 250, 300, 350, and 400 μmol / L.
[0037] Examples 26 to 32 are applications of iron-doped carbon nitride rich in nitrogen vacancies disclosed in the present invention. The difference from Example 1 is that in S3, the reaction temperature of the photocatalytic degradation reaction is controlled to be 10, 15, 20, 30, 35, 40, or 45°C.
[0038] Examples 32 to 39 are applications of iron-doped carbon nitride rich in nitrogen vacancies disclosed in the present invention. The difference from Example 1 is that in S3, the reaction pH of the photocatalytic degradation reaction is controlled to be 3, 4, 5, 6, 7, 8, 9, or 11.
[0039] Embodiments 40 to 43 are applications of iron-doped carbon nitride rich in nitrogen vacancies disclosed in the present invention. The difference from Embodiment 1 is that in S3, Fe-gC 3 N 4 Fe-gC obtained by replacing S1 with Nv 3 N 4 -Nv. Comparative Example
[0040] Comparative Example 1: An application of an iron-doped carbon nitride rich in nitrogen vacancies disclosed in the present invention. The difference from Example 1 is that in S3, Fe-gC 3 N 4 -Nv, no NaClO or NH 2 Cl, thus forming a UV-LED degradation system.
[0041] Comparative Example 2: An application of an iron-doped carbon nitride rich in nitrogen vacancies disclosed in the present invention. The difference from Example 1 is that in S3, Fe-gC 3 N 4 -Nv, without UV-LED irradiation, forms NaClO or NH 2 Cl degradation system.
[0042] Comparative Example 3: An application of an iron-doped carbon nitride rich in nitrogen vacancies disclosed in the present invention, which is different from Example 1 in that in S3, NaClO or NH 2 Cl, without UV-LED irradiation, forms Fe-gC 3 N 4 -Nv degradation system.
[0043] Comparative Example 4: An application of iron-doped carbon nitride rich in nitrogen vacancies disclosed in the present invention. The difference from Example 1 is that in S3, Fe-gC 3 N 4 -Nv, that is, UV-LED / NaClO or UV-LED / NH 2 Cl degradation system.
[0044] Comparative Example 5: An application of iron-doped carbon nitride rich in nitrogen vacancies disclosed in the present invention, which is different from Example 1 in that in S3, NaClO or NH 2 Cl, forming UV-LED / Fe-gC 3 N 4 -Nv degradation system.
[0045] Comparative Example 6: An application of iron-doped carbon nitride rich in nitrogen vacancies disclosed in the present invention, which is different from Example 1 in that in S3, UV-LED irradiation is not used, that is, NaClO / Fe-gC is formed. 3 N 4 -Nv or NH 2 Cl / Fe-gC 3 N 4 -Nv degradation system. Performance testing
[0046] Experimental Example 1: Structural Characterization of Nitrogen Vacancy-Rich Iron-Doped Carbon Nitride Commercially available gC 3 N 4 , iron-doped carbon nitride (iron-doped carbon nitride rich in nitrogen vacancies (Fe-gC 3 N 4 -Nv)), and iron-doped carbon nitride (Fe-gC) rich in nitrogen vacancies prepared according to Example 1 of the present invention 3 N 4 -Nv) were subjected to X-ray diffraction, nitrogen adsorption-desorption test, pore size distribution test, and infrared spectrum test. The results are as follows Figures 1 to 4 shown.
[0047] Figure 1 gC3 N 4 、Fe-gC 3 N 4 and Fe-gC 3 N 4 X-ray diffraction pattern of -Nv. gC 3 N 4 、Fe-gC 3 N 4 and Fe-gC 3 N 4 -Nv samples have strong diffraction peaks at 2θ values of 13.1° and 27.4°, corresponding to the (100) and (002) crystal planes, respectively. The characteristic diffraction peak near 13.1° is related to the repeated s-triazine structure in the plane, while the characteristic diffraction peak near 27.4° is related to the layered accumulation of the π conjugated plane. 3 N 4 Compared with the samples, Fe-gC 3 N 4 and Fe-gC 3 N 4 The intensity of the characteristic diffraction peak at 27.4° in the X-ray diffraction pattern of the -Nv sample decreases, which is attributed to the incorporation of iron atoms into gC 3 N 4 The absence of diffraction peaks of iron oxides further confirmed that iron existed mainly in ionic form rather than in compound form, which indicated that iron and gC 3 N 4 There are interactions between the frameworks. The introduction of nitrogen vacancies did not affect the Fe-gC 3 N 4 of the crystal structure.
[0048] Figure 2 gC 3 N 4 、Fe-gC 3 N 4 and Fe-gC 3 N 4 -Nv nitrogen adsorption-desorption test results and pore size distribution diagram. 3 N 4 、Fe-gC 3 N 4 and Fe-gC 3 N 4 -Nv samples have a type IV adsorption isotherm with an obvious hysteresis loop and all have a mesoporous structure. 3 N 4 -Nv has a specific surface area of 43.2m 2 / g, while gC 3 N4 and Fe-gC 3 N 4 The specific surface area is only 9.23m 2 / g and 13.4m 2 / g. gC calculated using the BJH method 3 N 4 、Fe-gC 3 N 4 and Fe-gC 3 N 4 The average pore sizes of -Nv are 19.4nm, 19.6nm and 20.5nm, and the corresponding pore volumes are 0.08cm 3 / g, 0.09cm 3 / g and 0.25cm 3 / g. Iron doping has an effect on gC 3 N 4 The introduction of nitrogen vacancies did not lead to gC 3 N 4 The lattice collapses within the framework, but increases gC 3 N 4 Specific surface area of Fe-gC 3 N 4 The increase in the specific surface area of -Nv provides more active sites for the adsorption and photocatalytic degradation of target pollutants.
[0049] Figure 3 gC 3 N 4 、Fe-gC 3 N 4 and Fe-gC 3 N 4 Fourier transform infrared absorption spectrum of -Nv. gC 3 N 4 、Fe-gC 3 N 4 and Fe-gC 3 N 4 The very similar vibration bands and absorption peaks in the Fourier transform infrared absorption spectrum of -Nv indicate that the doping of iron and the introduction of nitrogen vacancies do not change the gC 3 N 4 Chemical structure of gC 3 N 4 The frame has strong stability. 3000~3500cm -1 The broad absorption band at 1200~1700cm is related to the OH stretching vibration formed by the amino group at the NH or edge aromatic ring and the surface adsorbed water. -1The absorption peak at 880cm corresponds to the stretching vibration of C=N, CN in the 3-s-triazine ring and CN outside the ring. -1 The smaller absorption peak at 808cm is caused by the NH deformation vibration of the uncondensed amino group. -1 The absorption peak at is related to the bending vibration of the 3-s-triazine ring, which proves the existence of the 3-s-triazine ring structure. 3 N 4 No absorption peaks related to iron oxides were observed in the Fourier transform infrared absorption spectrum of g-Nv, which further indicates that the iron sites are not embedded in Fe-O but may be doped into g-C in the form of Fe-N. 3 N 4 in the frame.
[0050] Figure 4 gC 3 N 4 、Fe-gC 3 N 4 and Fe-gC 3 N 4 -Nv electron paramagnetic resonance spectrum. gC 3 N 4 、Fe-gC 3 N 4 and Fe-gC 3 N 4 Clear electron paramagnetic resonance signals (g=2.003) were detected in all Fe-gC samples. The signal originated from the local unpaired electrons on the carbon atoms at the nitrogen vacancies. The electron paramagnetic resonance intensity is proportional to the concentration of unpaired electrons, and the signal intensity increases with the increase of the number of nitrogen vacancies. 3 N 4 The electron paramagnetic resonance signal of -Nv is significantly higher than that of gC 3 N 4 and Fe-gC 3 N 4 , which indicates that Fe-gC 3 N 4 -Nv provides more unsaturated sites, resulting in a large number of unpaired electrons.
[0051] Experimental Example 2: Effects of different degradation systems on the degradation efficiency of carbamazepine The degradation solution after degrading carbamazepine in S3 of Example 1 and Comparative Examples 1 to 6 was tested for content. The test results are as follows: Figure 5 shown.
[0052] Figure 5The removal efficiency of carbamazepine by different degradation systems. As shown in the figure, UV-LED irradiation alone only removed 2.9% of carbamazepine molecules within 20 minutes. The presence of amide bonds resulted in carbamazepine having strong resistance to UV degradation. 2 The removal rates of 10 mg / L carbamazepine by the Cl oxidation process were only 5.2% and 1.4%, respectively. Although the redox potential of NaClO is 1.64 V / NHE, it is still insufficient to destroy the chemical bonds of carbamazepine molecules. 2 The weak oxidizing property of Cl leads to the 2 The degradation of carbamazepine by Cl oxidation process is negligible. 3 N 4 The adsorption removal rate of carbamazepine by -Nv was only 3.0%. The UV-LED / NaClO process degraded carbamazepine by 24.3% under the combined action of non-selective HO· and highly selective RCS. 2 The removal rate of carbamazepine by the Cl process was only 12.1%, which was related to the low rate of generation of active species in the system. 3 N 4 -Nv system increased the removal rate of CBZ to 31.7%. 3 N 4 -Nv with NaClO and NH 2 The combined use of NaClO / Fe-gC 3 N 4 -Nv system and NH 2 Cl / Fe-gC 3 N 4 -Nv system had only 8.6% and 4.6% removal rates of carbamazepine, respectively. 2 Introduction of Fe-gC into Cl system 3 N 4 -Nv constructed a new heterogeneous photocatalytic system to achieve a significant improvement in the degradation of carbamazepine, UV-LED / NaClO / Fe-gC 3 N 4 -Nv system and UV-LED / NH 2 Cl / Fe-gC 3 N 4 The removal rates of CBZ by the -Nv system were as high as 98.4% and 67.2%, respectively.
[0053] Test Example 3: Different Fe-gC 3 N 4Effect of -Nv dosage on the degradation efficiency of carbamazepine The removal rate of the degradation solution after degrading carbamazepine in S3 of Examples 1, 11, 12, 15 and 17 was measured. The test results are as follows Figure 6 shown.
[0054] Figure 6 (a) Fe-gC 3 N 4 -Nv dosage and its effect on UV-LED / NaClO / Fe-gC 3 N 4 -Nv system degradation efficiency of carbamazepine. As shown in the figure, when Fe-gC 3 N 4 When the dosage of -Nv increased from 0.05g / L to 0.4g / L, the removal rate of carbamazepine increased from 51.9% to 100% within 20min. 3 N 4 -Nv dosage increases the number of active sites, efficient separation of photogenerated carriers and O 2 · - The generation of NaClO fully activated the system, significantly increased the yield of HO· and Cl·, and accelerated the UV-LED / NaClO / Fe-gC 3 N 4 -Degradation in Nv system.
[0055] Figure 6 (b) Fe-gC 3 N 4 -Nv dosage and UV-LED / NH 2 Cl / Fe-gC 3 N 4 -Nv system degradation efficiency of carbamazepine. As shown in the figure, when Fe-gC 3 N 4 When the dosage of Fe-gC was within the range of 0.05~0.3g / L, the removal rate of carbamazepine increased with the increase of the dosage of catalyst. 3 N 4 When the dosage of Fe-gC was 0.3 g / L, the removal rate of carbamazepine by the system was as high as 78.1%. 3 N 4 When the dosage of -Nv increased from 0.3g / L to 0.4g / L, UV-LED / NH 2 Cl / Fe-gC 3 N 4 The removal rate of carbamazepine by the -Nv system decreased by 3.9%. 3 N4 -Nv has reached saturation in the reaction system, and the excess Fe-gC 3 N 4 -Nv may also cause light shielding effect.
[0056] Experimental Example 4: Effect of different reaction pH on the degradation efficiency of carbamazepine The degradation solution after degrading carbamazepine in S3 of Examples 1 and 34 to 38 was subjected to removal rate content determination. The test results are as follows: Figure 6 shown.
[0057] Figure 7 (a) Effect of solution pH on UV-LED / NaClO / Fe-gC 3 N 4 -Nv system degradation of carbamazepine. As shown in the figure, when the pH increases from 7 to 9, the UV-LED / NaClO / Fe-gC 3 N 4 The removal rate of carbamazepine by the -Nv system decreased from 98.2% to 64.2%, and the alkaline condition significantly inhibited the degradation efficiency of carbamazepine by the system. When the pH was reduced to 5, the degradation of carbamazepine by the system reached 98.2% in 10 minutes.
[0058] Figure 7 (b) Effect of solution pH on UV-LED / NH 2 Cl / Fe-gC 3 N 4 -Nv system degradation of carbamazepine. As shown in the figure, when the pH increases from 5 to 9, the UV-LED / NH 2 Cl / Fe-gC 3 N 4 The removal efficiency of CBZ by -Nv system decreased from 69.5% to 41.0%.
[0059] Test Example 5: Fe-gC 3 N 4 Effect of recycling of -Nv on the energy efficiency of carbamazepine degradation The removal rate of the degradation solution after degrading carbamazepine in S3 of Examples 1, 40 to 43 was measured. The test results are as follows: Figure 6 shown.
[0060] Figure 8 (a) Fe-gC 3 N 4 -Nv recycling and reuse for UV-LED / NaClO / Fe-gC 3 N 4-Nv system degradation efficiency of carbamazepine. As shown in the figure, after 5 cycles of testing, UV-LED / NaClO / Fe-gC 3 N 4 The removal rate of carbamazepine by the -Nv system can still be as high as 91.4%, which is only 7.8% lower than the initial photocatalytic degradation experiment. It has a high degradation rate and stable recycling and reuse performance.
[0061] Figure 8 (b) Fe-gC 3 N 4 -Nv recycling and reuse for UV-LED / NH 2 Cl / Fe-gC 3 N 4 -Nv system degradation of carbamazepine. As shown in the figure, after 5 cycles of testing, UV-LED / NH 2 Cl / Fe-gC 3 N 4 The removal rate of carbamazepine by the -Nv system can still reach 57.0%, which is 10.2% lower than the initial photocatalytic degradation experiment. It also has a high degradation rate and stable recycling performance.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. An application of iron-doped carbon nitride rich in nitrogen vacancies, characterized in that: Based on the UV-LED / NaClO and / or UV-LED / NH2Cl degradation system, the application of the nitrogen vacancy-rich iron-doped carbon nitride in the degradation of pharmaceutically active compounds.
2. The use of an iron-doped carbon nitride rich in nitrogen vacancies according to claim 1, characterized in that: The preparation process of the iron-doped carbon nitride rich in nitrogen vacancies comprises the following steps: firstly dissolving urea and FeCl3·6H2O in deionized water and stirring and mixing, evaporating the water and then grinding, calcining in a muffle furnace, cooling and grinding after calcination, and then calcining in a tubular furnace under a nitrogen atmosphere, cooling and grinding after calcination to obtain the iron-doped carbon nitride rich in nitrogen vacancies.
3. The use of an iron-doped carbon nitride rich in nitrogen vacancies according to claim 2, characterized in that: The mass ratio of the urea to FeCl3·6H2O is 100:
1.
4. The use of an iron-doped carbon nitride rich in nitrogen vacancies according to claim 2, characterized in that: The calcination temperature of the muffle furnace calcination is ≥575°C, the heating rate is 1-10°C / min, and the calcination time is ≥4h.
5. The use of an iron-doped carbon nitride rich in nitrogen vacancies according to claim 2, characterized in that: The calcination temperature of the tubular furnace calcination is ≥650°C, the heating rate is 1-10°C / min, and the calcination time is ≥4h.
6. The use of an iron-doped carbon nitride rich in nitrogen vacancies according to claim 1, characterized in that: The pharmaceutically active compound is carbamazepine.
7. The use of an iron-doped carbon nitride rich in nitrogen vacancies according to claim 1, characterized in that: In the process of degrading the active pharmaceutical compound, the iron-doped carbon nitride rich in nitrogen vacancies is first added to a solution containing the active pharmaceutical compound and adsorbed by stirring under dark conditions, then NaClO and / or NH2Cl are added to form a degradation system, and a photocatalytic degradation reaction is carried out under UV-LED irradiation, and the iron-doped carbon nitride rich in nitrogen vacancies is recovered after the reaction is completed.
8. The use of the iron-doped carbon nitride rich in nitrogen vacancies according to claim 7, characterized in that: The concentration of the active pharmaceutical compound in the degradation system is 1-10 mg / L, the concentration of the iron-doped carbon nitride rich in nitrogen vacancies is 50-400 mg / L, and the concentration of Cl - The concentration is 25~400μmol / L.
9. The use of iron-doped carbon nitride rich in nitrogen vacancies according to claim 7, characterized in that: The UV-LED light source wavelength of the photocatalytic degradation reaction is 278nm, the reaction temperature is 10-45°C, the reaction pH is 3-11, and the reaction time is ≥20min.
10. The use of iron-doped carbon nitride rich in nitrogen vacancies according to claim 7, characterized in that: The specific implementation method of recovering the iron-doped carbon nitride rich in nitrogen vacancies is that after the reaction is completed, the reaction liquid of the degradation system is filtered, the filter residue is washed with deionized water and ethanol for multiple times, and then dried at 80° C. to recover the iron-doped carbon nitride rich in nitrogen vacancies.
Citation Information
Patent Citations
A method for preparing an iron-doped graphitic carbon nitride / graphene multifunctional nanocomposite material
CN111453804B
Method for treating antiepileptic drug in water by using novel photo-Fenton-like system
CN112158910A
Cited By
Preparation method of Fe / Nv-PCN piezoelectric material
CN120172464A